RELIGIOUS BEHAVIOR AND TRADE TITHE COMPLIANCE OF MUSLIMAH ENTREPRENEURS IN SURABAYA - Firdaus, M. Nuril; Ulum, Fahrur (DIVERSITY Logic Journal Multidisciplinary, 2023)
Background. Regarding the behavior of religiosity and compliance with trade tithes by Muslimah entrepreneurs of the Indonesian Muslim Women Entrepreneurs Association (hereinafter referred to as IPEMI) Surabaya is in accordance with the theory, but in the religious behavior variable, namely knowledge about trade zakat. They still do not fully understand the calculation, distribution, and timeliness are still different. -differs in implementation. In addition, indicators of zakat compliance are also not precise in the calculation, distribution, and implementation time. Research Purposes. Knowing and analyzing religiosity behavior which includes belief, experience/practice, appreciation, knowledge, and commitment to IPEMI in compliance with trade tithes. Research Methods. The research design used a qualitative descriptive approach with an inductive mindset. Snowball sampling technique for sampling. Data collection through documentation and interviews with 5 people, including the chairman, and four members of IPEMI East Java who are domiciled in Surabaya, and focused on IPEMI Surabaya entrepreneurs who are members of IPEMI East Java. Findings. Religious behavior which includes belief, experience and practice, appreciation, knowledge, and commitment at IPEMI Surabaya is very good, it's just that there are some members who still lack knowledge and understanding of trade zakat. Conclusion. Religious behavior and commitment at IPEMI Surabaya are very good in terms of knowledge and understanding of trade zakat so that it can be integrated in a complex way between religious knowledge, feelings, and religious actions related to trade zakat.